The potential for productive use of the digital service LearningApps in teaching foreign languages - Natalia A. Katalkina; Nadezhda V. Bogdanova (RUDN Journal of Informatization in Education)
Problem statement. The active development of distance technologies has had a serious impact on the field of education and led to the formation of a new digital educational environment in higher education. Features of the formation of foreign language competence with the help of online games have become the subject of study. The purpose of the study is to test the method of productive use by students of higher educational institutions of the LearningApps service in the process of teaching foreign languages. Methodology. The main methods chosen were questionnaires and sociological surveys related to the introduction of digital tools at the university, allowing to assess the attitude of all participants towards the introduction of online games in the process of learning foreign languages. Results. The study of the process of digital communication made it possible to evaluate the role of gamification of learning using online games using digital didactic platforms. Gaming technologies in the digital educational environment have shown their effectiveness in training students - future specialists in various fields. The use of gamification elements activates the cognitive activity of students and maintains their interest in the subject being studied. Conclusion. Interactive game simulators serve to develop algorithmic thinking of students in foreign language lessons. Gamification of the process of teaching foreign languages using the digital service LearningApps has shown that the productive use of this resource allows not only to speed up the process of automating grammatical skills, but also to develop the creative potential of students in the course of their independent creation of online games, as well as to ensure autonomy and individualization of learning process.